New Product at Point of Sales : Menthol ball - AY, NADİYE PINAR (My University, 2022)
Aim: Point of sales (POS) advertising bans had been legislated in many countries without adequate enforcement. The aim of this study is to identify new products and devices at POS that could facilitate tobacco or nicotine use. Method: Shadow reporting at POS methodology developed by Framework Convention Alliance was used to investigate the products sold in four commercially dense districts of Istanbul. POS in one kilometer radius were visited by walking tour at each district. The products their display and compliance with legislation were noted. Results: Out of 198 POS visited 31 sell a product called "menthol ball". These were tiny colorful balls of menthol mixed with other various aromas that are sold together with an instrument that stab the end of a standard cigarette and insert the ball into the cigarette. The POS closest to schools were more likely to stock metholl balls. Majority of the POS placed the menthol balls close to candies, mints, chewing gums at eye level of children, just below the cigarette shelf. Conclusion: Tobacco industry uses menthol to sustain addiction among adolescents. Menthol use in cigarettes was banned on 5th January 2020 in Turkey. Using menthol balls to "make your own cigarette" is a novel technique developed by the industry to appeal the youth. Public health community needs to be vigilant and take actions.
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Health Sciences; SOLUNUM SİSTEMİ; Klinik Tıp; Klinik Tıp (MED); RESPIRATORY SYSTEM; CLINICAL MEDICINE; Clinical Medicine (MED); Solunum Bakımı; Akciğer ve Solunum Tıbbı; Respiratory Care; Pulmonary and Respiratory Medicine; Smoking; Children; Health policy